Importance of ethics and internal audit of organizations (GEON Journal (Management, Organizations and Business), 2020)
The International Financial Auditing Standards are quality standards for conducting a financial audit, implemented by an Auditor or Statutory Auditor. The purpose of this review is to identify the importance of the auditor's role regarding financial and non-financial information, through a documentary investigation; It is identified that one of its main applications is the financial audit and the most important for companies, because it reflects the current situation in quantitative terms, and seeks to determine if there are differences with the audited and unaudited documents. It also seeks to determine what type of information is financial and what is the non-financial information that is relevant in our audit, for this reason the auditor must be too careful, because he will be able to find congruence, regarding the already audited financial information or the statements financial, and although you should not give an opinion on it, it is important to take it into account for your final report
Keywords: audit; Auditor; Auditor independence; External Audit; Internal Audit; public audit; accounting; accounting data; audit data; financial management; managerial accounting